Pengaruh Kepemimpinan dan Kepribadian Individu Terhadap Kinerja Karyawan - Suartini, Luh Made; Hartati, Putu Sri; Dewi, Ida Ayu Ssmita (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
In a company, employee performance must be given great attention, because employee performance is very important to achieve the company’s goals. Employee performance is influenced by many factors such as leadership and individual personality. This research aims to determine the influence of leadership and individual personality on the performance of PD Dharma Santika Tabanan employees. The research method used is quantitative. The research location is PD Dharma Santika Tabana. The sample used was 33 respondents. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Determination Coefficient, T Test and F Test.Based on the research results, it was found that leadership had a significant positive effect on employee performance as evidenced by the tcount = 4.860 and significance value = 0.000, individual personality had a significant positive effect on employee performance as evidenced by the tcount = 2.911 and significance value = 0.007, and simultaneously leadership and Individual personality has a positive and significant effect on employee performance as evidenced by the F value = 38.608 and significance value = 0.000. The magnitude of the influence of the independent variable on employee performance is 70.2%.The suggestion in this research is that the leader of PD Dharma Santika Tabanan should before making a decision carry out a thorough and mature analysis so that he can make the right decision, give strict sanctions to employees who do not comply with the rules for arriving and leaving work and provide motivation to employees.